The Twin Instrument: Fertility and Human Capital Investment - Sonia R. Bhalotra; Damian Clarke (Institute of Labor Economics (IZA), 2018)
Twin births are often used to instrument fertility to address (negative) selection of women into fertility. However recent work shows positive selection of women into twin birth. Thus, while OLS estimates will tend to be downward biased, twin-IV estimates will tend to be upward biased. This is pertinent given the emerging consensus that fertility has limited impacts on women's labour supply, or on investments in children. Using data for developing countries and the United States, we demonstrate the nature and size of the bias in the twin-IV estimator of the quantity-quality trade-off and estimate bounds on the true parameter.
Keywords: J12; J13; C13; D13; I12; 330; twins; fertility; maternal health; quantity-quality trade-off; parental investment; bounds; IV